Patient-centered perspectives: A qualitative analysis of breast cancer patients' experiences with healthcare services - Fithrotin Azizah; Asri; Ira Purnamasari; Idham Choliq (Journal of Clinical Nursing Studies and Practice, 2025)
Breast cancer is a non-communicable disease with the highest prevalence in Indonesia that requires optimal health services. RSUD dr. Mohamad Soewandhie is one of the referral hospitals, but still faces obstacles such as long waiting times. This condition impacts patient comfort and satisfaction. Objective: This study aims to explore the experiences of breast cancer patients with health services at RSUD dr. Mohamad Soewandhie Surabaya. Method: This study used a descriptive qualitative method. Data were collected through in-depth interviews with breast cancer patients undergoing treatment at RSUD dr. Mohamad Soewandhie Surabaya. The data analysis technique used thematic analysis to identify themes based on patient experiences during treatment at RSUD dr. Mohamad Soewandhie. Results and Conclusions: The results of the study indicate that the experiences of breast cancer patients with health services at RSUD dr. Mohamad Soewandhie have 3 themes. In the sensory experience aspect, patients feel adequate facilities, a structured service schedule and physical comfort during treatment. In the emotional experience aspect, responses to the diagnosis vary with positive service assessments and hopes for improved service quality. In terms of social experience, the decision to choose a hospital is influenced by the referral system, distance from the location and availability of BPJS, and is supported by positive interactions between patients and medical personnel who provide meaningful experiences during the healing process.